Pelatihan Pembuatan Sabun Kertas Menggunakan Rice Paper: Meningkatkan Kemampuan Ekonomi dan Keterampilan Masyarakat - Satria Agung Novanto; Muhammad Rizqy Aji Kalyana; Farsya Audria Aisyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Training on making paper soap using rice paper in Kalijudan Village aims to improve the economic capacity and skills of the local community. Paper soap, as an innovative and environmentally friendly product, has huge market potential due to its ease of use. Through this training, participants are taught the process of making paper soap starting from selecting materials, printing techniques, to packaging the final product. It is hoped that this activity will not only be able to add new skills to the community, but also open up business opportunities that can increase household income. In addition, this training also supports environmental preservation by promoting the use of more environmentally friendly products. The results of this training show an increase in the knowledge and skills of participants who initially only knew about making paper soap from 0% of participants obtained from the pre-test to 100% obtained from the post-test as well as the potential for developing a paper soap business in Kalijudan Village.